Role-playing after 6 pm: conceptualization, scale development, and validation of formalistic overtime behavior in the Chinese workplace - Pengcheng Yang; Suchuan Zhang (Humanities & Social Sciences Communications)
Abstract As a typical stressor undermining employee well-being, unpaid overtime is prevalent in workplaces with weak labor protections. However, the practical tactics that employees adopt to cope with such illegitimate requirements remain under-explored in the existing literature. Focusing on the Chinese labor context, this study examines a nascent yet neglected impression management tactic: employees’ participation in performative work efforts during unpaid overtime, which we term Formalistic Overtime Behavior (FOB). This study integrates the literature on stress coping and impression management, establishes the conceptual foundation for the study of FOB and highlights its uniqueness. Through five studies involving six samples (N = 1451 Chinese adult full-time white-collar employees), we developed and validated a six-item FOB scale and preliminarily established its nomological network. Findings suggest that FOB is related to similar constructs (work withdrawal, workplace cheating, cyberloafing, facades of conformity, and surface acting) yet demonstrates unique characteristics. Moreover, illegitimate unpaid overtime exacerbates employees’ negative emotions and thus leads to FOB, especially under conditions of higher extra effort from colleagues. Further, FOB induces off-duty work-life conflict among employees, thus undermining positive affective work prospection on the next day. This study highlights the importance of FOB as a strategic coping approach with stress in unethical work contexts and its potential detrimental consequences for employees, thus providing insights for organizations to mitigate exploitative practices and promote ethical labor policies. Finally, theoretical and practical implications, limitations, and directions for future research are discussed.